Kecemasan pada Siswa Kelas 1 di SMP Dharma Wanita 9 Taman Sidoarjo: Pengembangan Instrumen - Ummu Umayyah; Aisyah Salsabila (Jurnal Al-Tatwir, 2019)
The current quantitative research was carried out to develop anxiety instruments from grand theories and detailed aspects into indicators to statement items representing theoretical constructs of anxiety in the form of blueprints. The data sampling technique employed in this study was purposive sampling. The subjects of the study were 98 respondents in total who attended the first grade of junior high school. The current study developed an anxiety instrument by employing aspects from Rosenhan and Seligman. SPSS used in the data analysis process. The data validity test stated that items number 6 and 20 were dropped because their scores were less than 0.300. Meanwhile, items number 1,2,3,4,5,7,8,9,10,11,12,13,14,15,16,17,18,19,21 were valid because their scores reached above 0,300. Moreover, from the reliability test, it was found that the score was 0.871 which implied that the data was reliable.